To the question about the place of organs of internal affairs in the law-enforcement system (Journal of actual problems of jurisprudence, 2018)
The theoretical questions of perfection of the law-enforcement system of Republic of Kazakhstan are examined in this article. Conclusion that law-enforcement activity is activity of the specially authorized public organs, providing an observance, guard and protection of rights and freedoms of citizens, legality and order, carried out by application of legal measures of influence in strict accordance with a law was made. It is also certain that a police is component part of the single system of Ministry of Internal affairs of Republic of Kazakhstan. Primary object of police is defense of life, health, rights and freedoms of human, providing of public law, property and public safety enforcement. A police carries out warning, suppression, exposure and opening of crimes and other offences. The analysis of current legislation of Republic of Kazakhstan is also conducted, namely laws on the organs of internal affairs and law on law-enforcement service. The recommendations sent to perfection of these laws are offered.Key words: personality, human rights, safety, law enforcement agencies, state, jurisprudence, police, law-enforcement bodies.